The Effect of Work Experience, Work Ethos, Training, and Improving Work Achievement on Employee Performance at PT PLN UP 3 Rantauprepat - Novridha Laylani; Siti Lam'ah Nasution; Abdul Halim (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The purpose of this study was to analyze the effect of work experience, work ethic, training and work performance improvement on employee performance at PT. PLN UP.3 Rantauprapat Labuhanbatu Regency, North Sumatra Province. Data collection techniques used in this study were observation, documentation and questionnaires using a Likert scale. The research population is the employees of PT. PLN UP.3 Rantauprapat as many as 86 people. Samples were taken using saturated sampling techniques using all populations as research subjects. The results of this study prove that work experience has a positive and significant effect on employee performance. Work Ethics has a positive and significant effect on Employee Performance. Training has a positive and significant effect on Employee Performance. Improved work performance has a positive and significant effect on employee performance. Work experience, work ethic, work performance improvement training simultaneously have a positive and significant effect on employee performance at PT. PLN UP.3 Rantauprapat. The R Square value from the analysis of the coefficient of determination is 0.696, meaning that employee performance (Y) can be explained by the variables of work experience (X1), work ethic (X2), training (X3) and increased work performance (X4) of 69.6%.